STRATEGIES TO INCREASE USER SATISFACTION IN ONLINE SHOPPING APPLICATIONS - Fariz, Fariz (Universitas Brawijaya, Indonesia, 2022)
This research was conducted to know the effect of Perceived Usability, Website Functionality, and Perceived Usefulness on Customer Satisfaction of Shopee application users in Surabaya. It is a basic research project that falls under causal research. A structural model was used in the quantitative research technique. Non-probability sampling utilizing the snowball sampling method was utilized. This research was conducted using a questionnaire to 100 people with online purchasing experience on Shopee, aged 15-34 years and residing in Surabaya were chosen as the sample criterion. Amos 21.0 software is used to process research data. Each variable, namely Perceived Usability, Website Functionality, and Perceived Usefulness, substantially affected Customer Satisfaction. There are some implications that Shopee can do, including paying attention to the quality of application usability in each of its uses. Such as speed in responding to customers in product searches, providing easy product recommendations based on purchase and search history, increasing customer data privacy policies, and providing a sense of security with black agreements. Above is white (digitally) that Shopee will maintain and not disseminate customer data to third parties, the quality of the Shopee application's speed to make payments easier and faster when the app is busy.